The influence of concrete compressive strength on the punching shear capacity of reinforced concrete flat slabs under different opening configurations and loading conditions. (October 2022) - Alrousan, Rajai Z.; Alnemrawi, Bara'a R.
Abstract: In this paper, theoretical and numerical approaches were used to investigate the punching shear capacity of RC flat slabs without shear reinforcement under the effect of loading eccentricity and the presence of an opening adjacent to the column face. Fourty-eight flat slabs of 1800 × 1800 × 120 mm 3 were analyzed, having different compressive strengths (30, 35, 40, and 45) MPa, loading eccentricities (0, 75, 150, and 225) mm, and opening configurations, including the opening existence and its location (with or opposite to the eccentricity side). No additional reinforcement was introduced after the opening was made to simulate the effect of an opening in an existing structure. The slabs were supported at 1500 mm in both directions using eight high-strength bolts and were analyzed up to failure under square column loading of 150 mm side. It was concluded that a linear relationship exists between the flat slab cracking, ultimate load capacity, and the concrete compressive strength under different loading eccentricity values. Furthermore, All simulated slabs failed in punching shear. Simulation results for all slabs were calculated using three different codes and compared to those obtained from the numerical simulation. It was found that all the codes underestimated the punching shear capacity of the investigated slabs. In addition, it was proved that the opening location with respect to the eccentricity side significantly affects the behavior of the flat slab, while all the international codes neglect this position.